Market Trends for US Berry Crops: Implications for Florida Blueberry, Blackberry, and Raspberry Producers: FE1123/FE1123, 11/2022 - Morgan, Kimberly L. (EDIS, 2022)
This publication presents production and market data specific to US blueberry, blackberry, and raspberry, with the intent to characterize related supply and demand trends recorded from 2000 to 2021. Implications from this market analysis are useful to inform production, harvest, and marketing decisions of Florida growers interested in, or involved with, the commercial berry industry. Written by Kimberly L. Morgan, and published by the UF/IFAS Food and Resource Economics Department, November 2022.